Evaluation of White Salted Noodles Enriched with Oat Flour - Mitra, Sabori; Cato, L.; James, Anthony; Solah, Vicky (American Association of Cereal Chemists, Inc, 2012)
Oat consumption is regarded as having significant health benefits. The enrichment of white salted noodles with oat flour would provide a potential health benefit but may affect the texture and sensory quality. Oat cultivars grown in Western Australia (Yallara, Kojonup, Mitika, Carrolup, and new line SV97181-8) and a commercial oat variety were milled into flour and added to wheat flour at 10, 20, and 30% to produce oat-enriched white salted noodles. The purpose of the study was to determine the quality characteristics of the oat flours and to assess the influence the oat flour blends had on noodle texture, color, and sensory characteristics. In addition, another goal was to determine whether the different oat cultivars had similar potential to provide health benefits by measuring the β-glucan content before and after processing. The results indicated that protein, ash content, and noodle firmness increased with the increased percentage of oat flour in the noodle formulations, whereas the pasting properties of the noodle wheat–oat flour blends did not differ significantly. The color of raw noodle sheets and boiled noodles changed significantly with oat incorporation and resulted in lower lightness/brightness, higher redness, lower yellowness, and lower color stability in comparison to standard wheat white salted noodles. Noodles made with the lowest oat percentage (10%) scored highest for all sensory parameters and were significantly different in appearance, color, and overall acceptability compared with noodles made with 20 and 30% oat flour.The β-glucan content of the flour blends increased with the increase in the level of oat incorporation but subsequently decreased during processing into noodles. The decrease in the β-glucan content varied across the different oat cultivars and levels of incorporation into the noodles. A new oat cultivar, SV97181-8, exhibited the least β-glucan loss during processing. In this study, the quality characteristics of white salted noodles enriched with oat flour from Western Australian cultivars were determined to provide essential information for the commercial development of healthier noodles.